2021
DOI: 10.1108/par-09-2020-0159
|View full text |Cite
|
Sign up to set email alerts
|

Coping with the COVID-19 crisis: an analysis of Twitter communication of companies

Abstract: Purpose The purpose of this paper is to investigate how New Zealand listed companies communicate COVID-19 related concerns on Twitter during the pandemic through various coping expressions and strategies. Design/methodology/approach A thematic content analysis was conducted to analyse COVID tweets based on Gaspar et al.’s (2016) coping strategy framework. Findings Six major COVID-19-related concerns communicated by New Zealand companies were found, with product/service being the most tweeted concern. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The results show that companies mostly publish a series of content that are not precisely those that generate the most interaction. Companies published more content related to the economy, the company itself or collaboration issues, as other recent studies have observed (Chong & Momin, 2021). However, stakeholders showed more interest and interaction when talking about others.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The results show that companies mostly publish a series of content that are not precisely those that generate the most interaction. Companies published more content related to the economy, the company itself or collaboration issues, as other recent studies have observed (Chong & Momin, 2021). However, stakeholders showed more interest and interaction when talking about others.…”
Section: Discussionsupporting
confidence: 54%
“…& Miquel, S. Thematic dis/connection of Ibex35 companies to generate dialogue with their stakeholders via Twitter during the pandemic social networks by Spanish teams during the pandemic were related to aspects linked to CSR and purpose, focusing more on aspects related to sponsorship or personal engagement (López-Carril & Anagnostopoulos, 2020). In a study conducted in listed companies in New Zealand, it was observed that product/service related information was the most tweeted concern and that the main strategy was based on information sharing (Chong & Momin, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Apart from factors like information technology (IT) alignment, trust and information sharing are known to be critical predictors of better supply chain resilience, as Naghshineh and Lotfi ( 2019 ) found in their study. But due to the spread of misinformation or fake news, especially during turbulence, trust is hampered, and the flow of information sharing is impacted (Chong & Momin, 2021 ). As a result, supply chain resilience is affected, which is perceived to adversely impact organizations’ supply chain agility and adaptability, adversely impacting on their practices and processes (Akter et al, 2016 ; Tan et al, 2017 ; Wamba et al, 2019 ).…”
Section: Theoretical Underpinning and Development Of Hypothesesmentioning
confidence: 99%
“…While the Internet provides a space for the unilateral provision of accountability (Agostino et al , 2021; Gallhofer and Haslam, 2006), social media are more interactive tools that not only facilitate the discharge of accountability but also stakeholders’ dialogue, engagement and participation (Agostino and Sidorova, 2017; Bellucci and Manetti, 2017; Manetti and Bellucci, 2016; Manetti et al , 2017; Bellucci et al , 2019). Indeed, recent research on accountability during COVID-19 has found that social media have been increasingly introduced by various types of organizations and institutions to discharge their accountability and to engage and prompt their stakeholders (Landi et al , 2021; Li et al , 2021; Chong and Momin, 2021). Findings also reveal that it has been increasingly used as a replacement for citizens’ daily social interaction and debate, with Facebook leading this upsurge (Trevisan et al , 2021).…”
Section: Introductionmentioning
confidence: 99%